Luminous Chromatics: Unveiling the Synergy of Light and Color in Visual Perception: Kromatika Cahaya: Mengungkap Sinergi Cahaya dan Warna dalam Persepsi Visual. - Muxamadiyev , Muxamadiyev; Xasanova , Xasanova (Indonesian Journal of Innovation Studies, 2024)
This scientific inquiry delves into the symbiotic relationship between light and color within the realm of design, elucidating their profound impact on visual perception. Employing a qualitative analysis of the interplay between these fundamental elements, our study reveals the unmistakable vibrancy and ubiquitous presence of light and color across all surfaces. The consistent presence of color not only illuminates but also augments the visibility of surrounding elements, thereby endowing a defining characteristic that facilitates color perception in the presence of light. Our findings underscore the intricate dynamics between light and color, opening avenues for further exploration in the nuanced field of visual aesthetics and design principles. Highlights: Harmony in Design: Investigates the interplay between light and color, emphasizing their harmonious integration in design aesthetics. Vibrant Visual Presence: Examines the unequivocal and vibrant manifestation of light and color across all surfaces, contributing to a visually compelling environment. Enhanced Visibility: Highlights the role of color in consistently illuminating and enhancing visibility, providing a crucial characteristic for color perception in the presence of light. Keywords: Light, Color, Design, Visual Perception, Synergy